HUBUNGAN RIWAYAT STATUS GIZI PADA IBU HAMIL DAN RIWAYAT PEMBERIAN ASI EKSKLUSIF DENGAN KEJADIAN STUNTING PADA BALITA USIA 2-5 TAHUN DI PUSKESMAS BONTANG SELATAN 2 - Mega Widia Rusti; M.H. Supriadi B; Diah Setiani (Journal of Innovation Research and Knowledge, 2023)
Introduction : One of the nutritional problems that occurs quite often is stunting. The incidence of stunting at the South Bontang 2 Community Health Center is in the high category, because it is still above 20%. The results of observations on 5 stunted toddlers were that 4 were not exclusively breastfed and there were 3 stunted toddlers whose mothers experienced CED during pregnancy. The aim of the research was to determine the relationship between the history of nutritional status in pregnant women and the history of exclusive breastfeeding with the incidence of stunting in toddlers at the South Bontang 2 Community Health Center. Methods: This type of research is analytical observation with a cross sectional research design. The population was 572 children aged 2-5 years who visited the South Bontang 2 Community Health Center, based on the Slovin formula, the sample size was 85 people. The sampling technique uses purposive sampling. Research instruments include questionnaires, observation sheets, KIA books and weight scales. Data analysis using Chi-Square. Results: The nutritional status history of pregnant women with toddlers was found to be normal (63.5%) and Chronic Energy Deficiency (CED) during pregnancy (36.5%). The history of exclusive breastfeeding for toddlers resulted in exclusive breastfeeding (67.1%) and not exclusive breastfeeding (32.9%). The incidence of stunting in toddlers was found to be normal (57.6%) and stunting (42.4%). There is a relationship between the history of nutritional status in pregnant women and the incidence of stunting in toddlers (p value 0.014) and there is a relationship between the history of exclusive breastfeeding and the incidence of stunting in toddlers (p value 0.002). Conclusion: There is a relationship between the history of nutritional status in pregnant women and the history of exclusive breastfeeding with the incidence of stunting in toddlers. It is recommended that nurses increase education regarding the incidence of stunting in toddlers